2020
DOI: 10.1016/j.jcte.2020.100237
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HbA1c reduction with FreeStyle Libre flash glucose monitoring (FLARE-NL 5)

Abstract: Aims To identify factors predicting HbA1c reduction in patients with diabetes mellitus (DM) using FreeStyle Libre Flash Glucose Monitoring (FSL-FGM). Methods Data from a 12-month prospective nation-wide FSL registry were used and analysed with multivariable regression. For the present study we included patients with hypoglycaemia unawareness or unexpected hypoglycaemias (n = 566) and persons who did not reach acceptable glycaemic control (HbA1c > 70 mmol/mol (8.5%)) (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
7
5
0
Order By: Relevance
“…The reduction in the A1C levels in our study at 6 and 12 months (−0.54% [−5.9 mmol/mol] and −0.42% [−4.6 mmol/mol], respectively) after the start of isCGM is in line with previous real-world studies ( 9 , 14 ). Tyndall et al ( 10 ) demonstrated a −0.37% (−4 mmol/mol) decrease in A1C in a prospective cohort of 900 patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reduction in the A1C levels in our study at 6 and 12 months (−0.54% [−5.9 mmol/mol] and −0.42% [−4.6 mmol/mol], respectively) after the start of isCGM is in line with previous real-world studies ( 9 , 14 ). Tyndall et al ( 10 ) demonstrated a −0.37% (−4 mmol/mol) decrease in A1C in a prospective cohort of 900 patients.…”
Section: Discussionsupporting
confidence: 93%
“…As seen in other studies ( 8 , 9 , 14 , 17 ), the patients in our study with poor glucose control (baseline A1C >9% [75 mmol/mol]) benefited the most from initiation of isCGM (A1C reduction −0.97% [−10.6 mmol/mol] at 12 months). In a subgroup analysis, patients with poor glycemic control (A1C >9% [75 mmol/mol]) before starting isCGM maintained the achieved A1C level for a longer time period.…”
Section: Discussionsupporting
confidence: 83%
“…A recent study evaluating the implementation of home delivery of medication for various illness during the COVID-19 pandemic found that patients and providers preferred the continuance of this approach, with overall improvements in patient adherence to medication 47 . The eHealth model observed a clinically relevant reduction of HbA1c 48 . In a systematic review conducted to determine the effectiveness of telemedicine in the delivery of diabetes care in low- and middle-income countries 10 , telemedicine yielded significant reductions in HbA1c, with interventions via telephone and short message service yielding the highest treatment effects 10 .…”
Section: Discussionmentioning
confidence: 91%
“…In addition to CSII, many DIYAPS use flash (intermittently scanned) CGM (isCGM) such as FreeStyle Libre (FSL). This is an alternative to conventional finger‐prick testing and measures interstitial glucose concentrations 14,15 . Previously conducted studies on the use of FSL have demonstrated reduction of time spent in hypoglycaemia, lower frequency of hypoglycaemic events and greater satisfaction 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…This is an alternative to conventional finger-prick testing and measures interstitial glucose concentrations. 14,15 Previously conducted studies on the use of FSL have demonstrated reduction of time spent in hypoglycaemia, lower frequency of hypoglycaemic events and greater satisfaction. 16,17 Given the described benefits, combining isCGM or CGM with insulin pump therapy might be expected to yield significant benefits to the user without the addition of an APS algorithm.…”
Section: Introductionmentioning
confidence: 99%